Physical, mechanical and electrical properties of Chitosan/Graphene Oxide composite films for copper ions (Cu2+) detection - Mohd Abdull Majid, Mohammad Abdull Halim; Osman, Nurul Huda; Tamchek, Nizam; Ahmad Sukri, Nurul Asyikin; Mazlan, Hazeem Ikhwan; Mazu, Nurul Najiha; Idris, Adilah; Liew, Josephine Ying Chyi; Ramli, Muhammad Mahyiddin (Springer, 2023)
Copper ions are one of the metal ions that contribute significantly to water pollution and threaten the ecosystem. The threat heightened the importance of the detection and removal of the contaminants. In this study, the Chitosan/Graphene Oxide (CH/GO) composite film was synthesized at different GO ratios via a direct casting technique. The structural, mechanical and film adsorption capacities were characterized along with the electrical properties. The results revealed that adding GO into CH at a 1:5 ratio produces the highest strength and adsorption capacity. The 1:5 film was then tested for its electrical properties to see the possibility of utilizing it as part of an electrical measurement system. Various electrical parameters such as permittivity (ε′, ε″), Tanδ, bulk resistivity (Rb) and DC conductivity (σDC) were studied. Results show that the 1:5 ratio chitosan film in various Cu2+ concentrations yielded significant differences in electrical properties. The Rb and σDC gave the most significant results and can be used as Cu2+ detection parameters.